2015
DOI: 10.1371/journal.pone.0138077
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Root Community Traits as Indicator for Transformation of Tropical Lowland Rain Forests into Oil Palm and Rubber Plantations

Abstract: Conversion of tropical forests into intensely managed plantations is a threat to ecosystem functions. On Sumatra, Indonesia, oil palm (Elaeis guineensis) plantations are rapidly expanding, displacing rain forests and extensively used rubber (Hevea brasiliensis) agro-forests. Here, we tested the influence of land use systems on root traits including chemical traits (carbon, nitrogen, mineral nutrients, potentially toxic elements [aluminium, iron] and performance traits (root mass, vitality, mycorrhizal coloniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 55 publications
(52 reference statements)
0
55
0
Order By: Relevance
“…In our loam Acrisol soil, which had lower soil fertility (i.e., lower Bray-extractable P and base saturation and higher Al saturation) than the clay Acrisol soil (Table A1; Allen et al, 2015), there may be strong competition for P such that trees have to allocate more C to their root or rootmycorrhizal system to obtain this nutrient. At the same study sites, reference land-use types on loam Acrisol soil showed a lower P concentration in the fine roots in the top 0.2 m of soil than reference land-use types on clay Acrisol soil (Sahner et al, 2015). This strategy of high belowground C investment was reflected in the negative correlation of annual soil CO 2 fluxes from the reference land-use types with Brayextractable P contents in the loam Acrisol soil.…”
Section: Co 2 and Ch 4 Fluxes From The Reference Land-use Typesmentioning
confidence: 79%
See 1 more Smart Citation
“…In our loam Acrisol soil, which had lower soil fertility (i.e., lower Bray-extractable P and base saturation and higher Al saturation) than the clay Acrisol soil (Table A1; Allen et al, 2015), there may be strong competition for P such that trees have to allocate more C to their root or rootmycorrhizal system to obtain this nutrient. At the same study sites, reference land-use types on loam Acrisol soil showed a lower P concentration in the fine roots in the top 0.2 m of soil than reference land-use types on clay Acrisol soil (Sahner et al, 2015). This strategy of high belowground C investment was reflected in the negative correlation of annual soil CO 2 fluxes from the reference land-use types with Brayextractable P contents in the loam Acrisol soil.…”
Section: Co 2 and Ch 4 Fluxes From The Reference Land-use Typesmentioning
confidence: 79%
“…We are especially grateful to our Indonesian assistants, Edward Januarlin Siahaan, Nelson Apriadi Silalahi, Ardi, Fahrurrozy and Edi, as well as all the rangers of the protected forest areas. We also acknowledge the other members of project A05 (Allen et al, 2015; Kurniawan et al., unpublished data) for the soil physical and biochemical data (Table A1); projects B04 (Kotowska et al, 2015), B06 (Rembold et al, unpublished data) and B07 (Sahner et al, 2015) for the litterfall and root production, root nutrient concentrations and vegetation characteristics (Table A2); and project C07 (Euler et al, unpublished data) for information on land-use history. We also thank Norman Loftfield, Oliver van Straaten, Andrea Bauer, Kerstin Langs and Martina Knaust (Georg August University Göttingen, Germany) for their assistance with laboratory analyses.…”
mentioning
confidence: 99%
“…In addition, microorganisms play a key role in decomposing soil organic matter and mineralizing nutrients in soil [7]. It has been shown that rainforest conversion to plantations has negative effects on the biodiversity of fungi [8,9], protists [10], vertebrates [11], insects and plants [12][13][14], archaea [15], but not on bacterial diversity which increased [15,16]. Additionally, the microbial community composition was severely affected by these conversion processes with a high impact on Proteobacteria which showed an abundance decrease and Actinobacteria, which showed an abundance increase with increasing land use intensity [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Rainforest conversion strongly affects environmental processes, including soil organic carbon pools and soil erosion (Guillaume, Damris, & Kuzyakov, 2015), primary production of trees (Kotowska, Leuschner, Triadiati, Meriem, & Hertel, 2015), carbon dioxide and methane fluxes (Hassler et al, 2015), as well as nitrogen cycling and soil fertility (Allen, Corre, Tjoa, & Veldkamp, 2015). It has been shown that rainforest conversion strongly affects biomass, vitality, and mycorrhizal colonization of roots (Sahner et al, 2015), biodiversity and abundance of microorganisms (Krashevska, Klarner, Widyastuti, Maraun, & Scheu, 2015;Schneider et al, 2015) and trophic-guild composition of litter-dwelling fauna (Barnes et al, 2014;Klarner et al, 2017). It has been shown that rainforest conversion strongly affects biomass, vitality, and mycorrhizal colonization of roots (Sahner et al, 2015), biodiversity and abundance of microorganisms (Krashevska, Klarner, Widyastuti, Maraun, & Scheu, 2015;Schneider et al, 2015) and trophic-guild composition of litter-dwelling fauna (Barnes et al, 2014;Klarner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of conversion of rainforest into plantations on belowground organisms is less well studied. It has been shown that rainforest conversion strongly affects biomass, vitality, and mycorrhizal colonization of roots (Sahner et al, 2015), biodiversity and abundance of microorganisms (Krashevska, Klarner, Widyastuti, Maraun, & Scheu, 2015;Schneider et al, 2015) and trophic-guild composition of litter-dwelling fauna (Barnes et al, 2014;Klarner et al, 2017). However, the effect of rainforest conversion on food resources of soil fauna and the relative importance of energy channels of soil food webs (Moore et al, 2004) is little understood.…”
Section: Introductionmentioning
confidence: 99%